Evaluación de la iluminación en las áreas administrativas y postcosecha y su incidencia en la salud de los trabajadores en la empresa florícola NEVADO-ECUADOR. Diseño de una propuesta de intervención. - Arcos Barbosa, Marco Xavier (2014)
This research includes the study on the lighting conditions in the administrative job and postharvest in Nevado-Ecuador flower business areas, being a key factor for business environments. The methodological parameters for this research are based on identification, measurement, assessment , and risk control , using the UNE -EN 12464-1 , NOM -025- STPS- 2008 standards, given to establish lighting requirements for people and workplaces , analyzing of this research a deficit was determined in the average light level about , reflection factor that the majority of each jobs are into the recommended parameters in relation about uniformity degree is not into the proper range distribution , with regard about dose it has a deficit in its relation because it has minimum requirements lighting set, increasing the accident risk and causing deterioration in the health workers health , resulting about 66.66 % ocular discomfort, presenting the following symptoms: blurred vision, heaviness in the eyelids , tired vision , itching and redness eyes causing fatigue, headache, stress, , annoying reflections , shadows increased , lack of light uniformity , affecting their effectiveness performance in their activities development and their life quality. The design of the lighting in the workplace is oriented not only to the amount of light balance between the quality and, quantity, and stability and function of each activity and the work area which is done getting reflexes absence, excessive flicker and get contrasts to favor visual perception in order to ensure the proper execution an tasks and the safety and welfare who make them.